Barriers to CIM Implementation for SMEs in the Klang Valley - Lim, Thiam Lai (2004)
Small and Medium Enterprises (SMEs) in Malaysia play a very important role in the country's economic development. In the year 2002, SMEs comprised 90.0% of the total manufacturing establishments in Malaysia and contributing to 33.3% of total employment in the country. Undoubtedly, in the new millennium, the Malaysia SMEs will face new opportunities as well as challenges, particularly in view of the liberalization of trade and investment under the ASEAN Free Trade Area (AFTA), the ASEAN Investment Area (AIA), the European Union (EU) and the emerging market economies of Eastern Europe and China. The increasing global competition, technology advances, social changes, changes in government trade and investment policies and changing consumers markets will be some of the difficulties facing the Malaysian SMEs. Therefore, the SMEs must formulate and implement new strategies that will enable them to cope with these new challenges. It is essential to conduct research and study on the Malaysian SMEs to provide useful information so to enhance effort to transform the manufacturing industry into a more dynamic sector with high value added, capital intensive, high technology as well as skill and knowledge intensive industries. The purpose of this study is to investigate how the SMEs perceive automation like computer integrated manufacturing system and how the factors like management mindset; company size and level of computer literate of the workforce can influence on the decision to implement computer integrated manufacturing, CIM. This study gathered information on the barriers of implementing CIM. The research is an empirical study on the SMEs within Klang Valley. The method of the research is the questionnaire survey method. A total of 290 questionnaires were mail to the selected SMEs companies listed in the SMI Directory 2001 and the FMM Directory 2001. Selection of SMEs was based on stratified sampling method on the basis of 25%. A total of 56 responses were collected and data was analysed using SPSS version-10.0 software Analysis techniques used were the test of correlation (Chi-square) and linear regression. Result of the findings shows that the management understanding and knowledge of CIM and level of computer literate operator has a significant influence to the decision to implement CIM. But, the size of company does not have significant influence on the implementation of CIM. The findings also indicate that to improve the adaptation of CIM, SMEs needs to improve the level of computer integration. Training has been identified as the key issue before the implementation of CIM. Therefore, in order to make implementation successful in SMEs a comprehensive and effective training program is required.